Analisis Kinerja Pemasaran PT. NSS - Edwin Kanadi; M.Y. Dwi Hayu Agustini (JEMAP, 2018)
NSS Limited Liability Company (NSS LLC) is a lubricant product distributor which has distribution permit from principal of a certain area. The company should maintain a certain performance as the principal’s criteria. Effort to maintain company’s marketing performance always should be conducted sothat to hold the distribution permit. This research aimed to analyze the marketing performance of NSS LLC based on 4Ps elements of marketing mix. Data were collected from 50 active consumers which routinely purchase in six month lately with questionnaires. Desciptive analyze was used to depict the company’s marketing  performance with tables and using average. Overall, results showed that NSS LLC’s marketing performance were good. Each marketing mix element was scored good by consumers. Place distribution element was scored the best compared to other elements, especially related to product guarentee to reach the consumers’ hands in good condition and on exact time. Whilst promotion as the  marketing mix element  was scored the lowest, though promotion programs were scored interesting and frequently conducted.